Clusterin enhances AKT2‐mediated motility of normal and cancer prostate cells through a PTEN and PHLPP1 circuit. Issue 7 (22nd November 2018) - Bertacchini, Jessika; Mediani, Laura; Beretti, Francesca; Guida, Marianna; Ghalali, Aram; Brugnoli, Federica; Bertagnolo, Valeria; Petricoin, Emanuel; Poti, Francesco; Arioli, Jessica; Anselmi, Laura; Bari, Alessia; et al.
Abstract: Clusterin (CLU) is a chaperone‐like protein with multiple functions. sCLU is frequently upregulated in prostate tumor cells after chemo‐ or radiotherapy and after surgical or pharmacological castration. Moreover, CLU has been documented to modulate the cellular homolog of murine thymoma virus akt8 oncogene (AKT) activity. Here, we investigated how CLU overexpression influences phosphatidylinositol 3′‐kinase (PI3K)/AKT signaling in human normal and cancer epithelial prostate cells. Human prostate cells stably transfected with CLU were broadly profiled by reverse phase protein array (RPPA), with particular emphasis on the PI3K/AKT pathway. The effect of CLU overexpression on normal and cancer cell motility was also tested. Our results clearly indicate that CLU overexpression enhances phosphorylation of AKT restricted to isoform 2. Mechanistically, this can be explained by the finding that the phosphatase PH domain leucine‐rich repeat‐containing protein phosphatase 1 (PHLPP1), known to dephosphorylate AKT2 at S474, is markedly downregulated by CLU, whereas miR‐190, a negative regulator of PHLPP1, is upregulated. Moreover, we found that phosphatase and tensin homolog (PTEN) was heavily phosphorylated at the inhibitory site S380, contributing to the hyperactivation of AKT signaling. By keeping AKT2 phosphorylation high, CLU dramatically enhances the migratory behavior of prostate epithelial cell lines with different migratory and invasive phenotypes, namely prostate normal epithelial 1A (PNT1A) and prostatic carcinoma 3 (PC3) cells. Altogether, our results unravel for the first time a circuit by which CLU can switch a low migration phenotype toward a high migration phenotype, through miR‐190‐dependent downmodulation of PHLPP1 expression and, in turn, stabilization of AKT2 phosphorylation. Abstract : In human prostate cells, clusterin (CLU) overexpression was found to enhance the phosphorylation of AKT restricted to isoform 2. Mechanistically, this was explained by the finding that the phosphatase PHLPP1, known to dephosphorylate AKT2 at S474, is markedly downregulated by CLU, whereas miR‐190, a negative regulator of PHLPP1, is upregulated. Moreover, we found that PTEN was heavily phosphorylated at the inhibitory site S380, contributing to the hyperactivation of AKT signaling. Remarkably, we also demonstrated that by keeping AKT2 phosphorylation high, CLU dramatically enhances the migratory behavior of prostate epithelial cell lines with different migratory and invasive phenotype, namely PNT1A and PC3 cells.